The impact of foreign interventions on democracy and human rights - Figueroa, Ana Magdalena (Emerald Publishing Limited, 2022)
The Impact of Foreign Interventions on Democracy and Human Rights is a provocative study exploring the relationship between military and economic interventions around the world. The book establishes what determines the success or failure of foreign interventions with respect to their initial goals of helping improve the quality of the democratic institutions in locations such as Latin America, Africa, and the Middle East. Using different methodologies ranging from quantitative methods to mixed methods as well as in-depth historical case studies, this volume profoundly analyses how military and economic interventions have affected the democratic institutions in those intervened countries. While some chapters are focused on cross-country analyses, other chapters provide a more in-depth case analysis of interventions and its effects on the target country including Libya, the Democratic Republic of Congo, Somalia, Nicaragua, Cuba, and Brazil. With authors coming together from political science, international relations, and international political economy, The Impact of Foreign Interventions on Democracy and Human Rights provides a holistic view establishing the differences between the policies, methods, intentions, and consequences of the various American, French, and Chinese interventions in the case studies they present.
Keywords: Intervention (International law); Human rights.; Democracy.; Political Science -- International Relations -- General.; Public international law.; elektronické knihy; electronic books